Promoción y turismo gastronómico del cantón Guano, provincia de Chimborazo. - López Santana, Liz Estefania (2023)
ABSTRACT: Tourism is one of the sectors most affected by the Covid-19 pandemic in Ecuador, so once we had overcome this phase, tourism must be revived , since it is an important source of country income . The aim of the present research work is to identify if there is a relationship between promotion and gastronomy tourism in Guano canton , Chimborazo province, a mixed approach was applied , of a descriptive and correlational type, of a nonexperimental and bibliographic research, was applied. in which surveys to the owners of the gastronomic centers of the La Matriz parish and to the officials of the GADM of Guano, reflecting that the promotion is a dynamic and viable tool for the development of gastronomy tourism in this place. Finally, some business strategies are proposed to encourage the gastronomy tourism in Guano.